Multiple Pipeline Embolization Devices for the Treatment of Complex Intracranial Aneurysm: A Multi-Center Study - Fan, Feng; Fu, Yu; Liu, Jianmin; Yang, Xinjian; Zhang, Hongqi; Li, Tianxiao; Shi, Huaizhang; Wan, Jieqing; Zhao, Yuanli; Wang, Yunyan; Feng, Wenfeng; Song, Donglei; et al. (Frontiers in Aging Neuroscience, 2022)
Background: The Pipeline for Uncoilable or Failed Aneurysms (PUFS) trial primarily demonstrated the safety and efficacy of the implantation of multiple pipeline embolization devices (multi-PEDs) for large/giant intracranial aneurysms. However, no study has focused on when, why, or how to apply multi-PEDs. Objective: To investigate the indications and strategies of using multi-PEDs for complex intracranial aneurysms. Methods: Patients who had been treated with two or more PEDs were included in the post-market multicenter registry study from 2014 to 2019, across 14 centers in China. Indications, strategies, perioperative safety, and clinical outcomes were retrospectively analyzed. The modified Rankin scale (mRS) score was used to evaluate clinical outcomes comprehensively, and the O’Kelly‒Marotta (OKM) grading scale was used to evaluate aneurysm healing results. Results: Fifty-five intracranial aneurysms were treated with multi-PEDs. There were 20 fusiform aneurysms with a large range, 25 large/giant saccular aneurysms, six aneurysms with failed treatment, and four aneurysms with greatly varied diameters of the parent artery. The strategies included telescope techniques in 40 patients and overlap techniques in 15 patients. In total, 120 stents were deployed in 55 patients. The operation styles included 25 patients (55.6%) with two PEDs, 21 patients (38.2%) with two PEDs combined with coiling, four patients (7.3%) with three PEDs, four patients (7.3%) with three PEDs combined with coiling, and one patient (1.8%) with four PEDs. Angiography revealed OKM D in two, OKM C in seven, and OKM A&B in 46 cases after surgery. During the perioperative period, eight patients developed neurological dysfunction, three of whom died. Thirty-four patients were followed up with digital subtraction angiography for 2–45 (8.2 ± 8.0) months. Angiography revealed OKM D in 26, OKM C in five, and OKM B in three. At the last follow-up, the mRS score was 0–1 in 52 patients. Conclusion: The treatment of anterior circulation aneurysms with multi-PEDs is safe and effective. The implantation of multi-PEDs could be considered for large-scale fusiform aneurysms, large/giant saccular aneurysms with a jet-sign, salvage of failed PED treatments, and in cases where the diameter of the parent artery varies greatly.